Myocardial infarction and stroke associated with diuretic based two drug antihypertensive regimens: population based case-control study. (25th January 2010) - Boger-Megiddo, Inbal; Heckbert, Susan R; Weiss, Noel S; McKnight, Barbara; Furberg, Curt D; Wiggins, Kerri L; Delaney, Joseph A C; Siscovick, David S; Larson, Eric B; Lemaitre, Rozenn N; Smith, Nicholas L; Rice, Kenneth M; et al.
Abstract : Objective To examine the association of myocardial infarction and stroke incidence with several commonly used two drug antihypertensive treatment regimens. Design Population based case-control study. Setting Group Health Cooperative, Seattle, WA, USA. Participants Cases (n=353) were aged 30-79 years, had pharmacologically treated hypertension, and were diagnosed with a first fatal or non-fatal myocardial infarction or stroke between 1989 and 2005. Controls (n=952) were a random sample of Group Health members who had pharmacologically treated hypertension. We excluded individuals with heart failure, evidence of coronary heart disease, diabetes, or chronic kidney disease. Exposures One of three common two drug combinations: diuretics plus β blockers; diuretics plus calcium channel blockers; and diuretics plus angiotensin converting enzyme inhibitors or angiotensin receptor blockers. Main outcome measures Myocardial infarction or stroke. Results Compared with users of diuretics plus β blockers, users of diuretics plus calcium channel blockers had an increased risk of myocardial infarction (adjusted odds ratio (OR) 1.98, 95% confidence interval 1.37 to 2.87) but not of stroke (OR 1.02, 95% CI 0.63 to 1.64). The risks of myocardial infarction and stroke in users of diuretics plus angiotensin converting enzyme inhibitors or angiotensin receptor blockers were slightly but not significantly lower than in users of diuretics plus β blockers (myocardial infarction: OR 0.76, 95% CI 0.52 to 1.11; stroke: OR 0.71, 95% CI 0.46 to 1.10). Conclusions In patients with hypertension, diuretics plus calcium channel blockers were associated with a higher risk of myocardial infarction than other common two drug treatment regimens. A large trial of second line antihypertensive treatments in patients already on low dose diuretics is required to provide a solid basis for treatment recommendations.